Mental health challenges, treatment experiences, and care needs of post-secondary students: a cross-sectional mixed-methods study - Elnaz Moghimi; Callum Stephenson; Gilmar Gutierrez; Jasleen Jagayat; Gina Layzell; Charmy Patel; Amber McCart; Cynthia Gibney; Caryn Langstaff; Oyedeji Ayonrinde; Sarosh Khalid-Khan; Roumen Milev; et al. (BMC, 2023)
Abstract Background Post-secondary students frequently experience high rates of mental health challenges. However, they present meagre rates of treatment-seeking behaviours. This elevated prevalence of mental health problems, particularly after the COVID-19 pandemic, can lead to distress, poor academic performance, and lower job prospects following the completion of education. To address the needs of this population, it is important to understand students' perceptions of mental health and the barriers preventing or limiting their access to care. Methods A broad-scoping online survey was publicly distributed to post-secondary students, collecting demographic, sociocultural, economic, and educational information while assessing various components of mental health. Results In total, 448 students across post-secondary institutions in Ontario, Canada, responded to the survey. Over a third (n = 170; 38.6%) of respondents reported a formal mental health diagnosis. Depression and generalized anxiety disorder were the most commonly reported diagnoses. Most respondents felt that post-secondary students did not have good mental health (n = 253; 60.5%) and had inadequate coping strategies (n = 261; 62.4%). The most frequently reported barriers to care were financial (n = 214; 50.5%), long wait times (n = 202; 47.6%), insufficient resources (n = 165; 38.9%), time constraints (n = 148; 34.9%), stigma (n = 133; 31.4%), cultural barriers (n = 108; 25.5%), and past negative experiences with mental health care (n = 86; 20.3%). The majority of students felt their post-secondary institution needed to increase awareness (n = 231; 56.5%) and mental health resources (n = 306; 73.2%). Most viewed in-person therapy and online care with a therapist as more helpful than self-guided online care. However, there was uncertainty about the helpfulness and accessibility of different forms of treatment, including online interventions. The qualitative findings highlighted the need for personal strategies, mental health education and awareness, and institutional support and services. Conclusions Various barriers to care, perceived lack of resources, and low knowledge of available interventions may contribute to compromised mental health in post-secondary students. The survey findings indicate that upstream approaches such as integrating mental health education for students may address the varying needs of this critical population. Therapist-involved online mental health interventions may be a promising solution to address accessibility issues.